ASSESSMENT OF THE PHYTOEXTRACTION POTENTIAL OF THIRTEEN PLANT SPECIES FOR CHROMIUM AND VANADIUM AND THEIR RELATIONSHIP WITH SULFUR AND HISTIDINE - Akkus, Sukran Ozen; Yaman, Burak; Yaman, Mehmet (Polish Society Magnesium Research, 2017)
The aim of this study has been to examine the phytoextraction potential of thirteen plant species for chromium (Cr) and vanadium (V) and their relationship with sulfur and histidine. The species including Juglans regia L., Platanus L., Pinus nigra L., Thuja (Cupressaceae), Salix matsudana, Cupressus arizonica, Eleagnus ang., Vitis vinifera, Nerium olean., Robinia pse., Populous nigra, Grasses and Cedrus libani were collected from two highly industrialized cities: Bursa and Gaziantep, in Turkey. The determinations were carried out by the ICP-MS and HPLC-MS methods. Concentrations of chromium and vanadium were in the ranges of 198-10 484 and 40-1100 mu g kg(-1), respectively. Concentrations of sulfur were in the range of 705-8762 mg kg(-1), while the concentrations of histidine were found to be between 1 and 33 mg kg(-1). The ratios of the highest to the lowest chromium concentrations for Salix, Nerium olean. and Thuja (Cupressaceae) were found to be 16.4, 12 and 12.9-fold, respectively. Similarly, the ratios of the highest to the lowest vanadium concentrations for plant species are 2.9-fold for Thuja, 4.1-fold for Pinus nigra, 5.9-fold for Vitis vin. and 3.5-fold for Robinia pseu. Thus, the plant species mentioned above may be considered as a biomonitor and/or having the hyperaccumulator potential for chromium and vanadium. This is the first study in the literature to explore the relationship between the concentrations of histidine and sulfur with chromium and vanadium for the analyzed plant samples. It can be concluded that increased chromium concentrations in Salix leaves stimulate sulfur related with amino acids in this plant.
Keywords: chromium; vanadium; sulfur; trees; ICP-MS